2019
DOI: 10.1107/s1600577519010543
|View full text |Cite
|
Sign up to set email alerts
|

Controllability of cupric particle synthesis by linear alcohol chain number as additive and pH control in cupric acetate solution using X-ray radiolysis

Abstract: Synthesis and immobilization of caltrop cupric particles onto a Si substrate using X-ray radiolysis directly from a liquid solution of Cu(COOCH3)2 is demonstrated. Caltrop cupric oxide particles are formed in the X-ray radiolysis of aqueous solutions of Cu(COOCH3)2, which also contain methanol, ethanol, 2-propanol or 1-propanol as ^\bulletOH scavenger. The blade lengths of the caltrop particles are dependent on the alcohol chain length. In particular, it was found that an alkyl alcohol whose chain length is lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…They also reported that the synthesized candy-like Cu 4 O 3 microstructure exhibits good long-term antibacterial activities to both E. coli and S. aureus bacteria because the release of Cu 2+ ions from the Cu 4 O 3 is responsible for the antibacterial activity. On the other hand, Yamaguchi et al have added the X-ray-radiolysisinduced photochemical synthesis of copper oxide materials as liquid-based phase reaction (Yamaguchi et al, 2016a(Yamaguchi et al, ,b, 2017(Yamaguchi et al, , 2019Saegusa et al, 2019). Until now, a single Cu 4 O 3 phase has not been obtained by X-ray-irradiation of the liquid phase.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…They also reported that the synthesized candy-like Cu 4 O 3 microstructure exhibits good long-term antibacterial activities to both E. coli and S. aureus bacteria because the release of Cu 2+ ions from the Cu 4 O 3 is responsible for the antibacterial activity. On the other hand, Yamaguchi et al have added the X-ray-radiolysisinduced photochemical synthesis of copper oxide materials as liquid-based phase reaction (Yamaguchi et al, 2016a(Yamaguchi et al, ,b, 2017(Yamaguchi et al, , 2019Saegusa et al, 2019). Until now, a single Cu 4 O 3 phase has not been obtained by X-ray-irradiation of the liquid phase.…”
Section: Resultsmentioning
confidence: 99%
“…We performed synchrotron-radiation-induced X-ray radiolysis experiments using beamline BL8S2 at the Aichi Synchrotron Radiation Center, Aichi Science and Technology Foundation (Yamaguchi et al, 2015(Yamaguchi et al, , 2016a(Yamaguchi et al, ,b, 2017(Yamaguchi et al, , 2019Saegusa et al, 2019). The storage ring current and energy were in operation at 300 mA and 1.2 GeV with super-bending magnets of 5 T. The X-ray spectrum is displayed in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations